2007
DOI: 10.7863/jum.2007.26.10.1271
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantification of Tumor Vascularity as a Tertiary Test After B-Mode and Power Doppler Evaluation for Detection of Ovarian Cancer

Abstract: In masses with central vascularization on 2-dimensional power Doppler sonography, the use of 3D quantification of tumor vascularity had low diagnostic accuracy in the detection of adnexal malignancies, although an increase in accuracy in masses with a solid portion of greater than 10 mL was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…These scoring systems have been evaluated, but a completely reliable differentiation of malignant masses is not possible by sonography alone. 3,[20][21][22][23][24][25][26][27] The simple rules by the international ovarian tumor analysis group and various modifications of the risk of malignancy index have been evaluated in several studies for differentiating between benign and malignant adnexal masses. Two-step and three step triage strategies have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These scoring systems have been evaluated, but a completely reliable differentiation of malignant masses is not possible by sonography alone. 3,[20][21][22][23][24][25][26][27] The simple rules by the international ovarian tumor analysis group and various modifications of the risk of malignancy index have been evaluated in several studies for differentiating between benign and malignant adnexal masses. Two-step and three step triage strategies have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…37 There is limited evidence with use of three dimensional and power Doppler indices for detection of malignancy. 21,38,39 Studies have demonstrated three dimensional power doppler indices to have a positive correlation with serum VEGF levels in ovarian masses. 21,38 Preoperative serum levels of vascular endothelial growth factor (VEGF) were correlated with three dimensional power Doppler indices in ovarian masses and the vascularization index (VI), flow index (FI) and vascularization flow index (VFI), correlated positively with serum VEGF levels, which were higher in malignant ovarian masses than in benign masses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Guerriero et al found that the use of 3D PD increased the specificity of ultrasound in suspicious masses but also decreased significantly the sensitivity. 75 These studies are summarized in Table 4.…”
Section: Adnexal Tumorsmentioning
confidence: 99%
“…L'utilisation de produit de contraste n'est pas validée pendant la grossesse et le 3D ne semble pas apporter d'amélioration de discrimination bénigne-maligne [23][24][25].…”
Section: Problème Diagnostiqueunclassified